2008
DOI: 10.1063/1.2937770
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear magnetohydrodynamics of pulsed parallel current drive in reversed-field pinches

Abstract: Nonlinear simulation with a simple resistive magnetohydrodynamics model is used to investigate the stabilization of magnetic fluctuations in reversed-field pinch plasmas subject to pulsed-parallel current drive. Numerical results are diagnosed with computations of nonlinear power transfer and by evaluating sequences of profiles for linear stability. Results show that poloidal electric field pulsing promptly affects the exchange of energy between the mean profiles and both core-resonant m =1 fluctuations and hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…This study is an addition to the previous modelling of stabilization of core resonant (resonance surface is within the reversal surface) current-driven modes in RFP during PPCD [14,15] which explained their stabilization during the drive. The previous and present studies demonstrated stabilization of current-and pressure-driven modes during PPCD, thus explaining the significant improvement in plasma confinement.…”
Section: Introductionmentioning
confidence: 65%
“…This study is an addition to the previous modelling of stabilization of core resonant (resonance surface is within the reversal surface) current-driven modes in RFP during PPCD [14,15] which explained their stabilization during the drive. The previous and present studies demonstrated stabilization of current-and pressure-driven modes during PPCD, thus explaining the significant improvement in plasma confinement.…”
Section: Introductionmentioning
confidence: 65%
“…Good energy confinement in steady state RFP equilibrium will require a current drive profile aligned with the equilibrium current density, which can be tailored to stabilize the tearing fluctuations. This has been demonstrated transiently by PPCD [1].…”
Section: Introductionmentioning
confidence: 77%
“…This type of analysis has been useful for studying nonlinear MHD dynamics in RFPs, (e.g., Refs. [37] and [38] ). Here, the power transfer analysis shows slow growth phase of n = 1 is driven by multiple nonlinear interactions.…”
Section: Discussionmentioning
confidence: 98%